2016
DOI: 10.1186/s12967-016-1098-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polyglycerol is superior to glucose for long-term preservation of peritoneal membrane in a rat model of chronic peritoneal dialysis

Abstract: BackgroundReplacing glucose with a better biocompatible osmotic agent in peritoneal dialysis (PD) solutions is needed in PD clinic. We previously demonstrated the potential of hyperbranched polyglycerol (HPG) as a replacement for glucose. This study further investigated the long-term effects of chronic exposure to HPG as compared to a glucose-based conventional PD solution on peritoneal membrane (PM) structure and function in rats.MethodsAdult male Wistar rats received once-daily intraperitoneal injection of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…PYS (Physioneal™ 40 solution, 2.27% glucose w/v) and ICO (Extraneal™, 7.5% icodextrin w/v) were purchased from Baxter Healthcare Co. (Deerfield, IL, USA). HPG (1 kDa) was synthesized by an anionic ring opening multibranching polymerization and characterized following our previous reports . A HPG PD solution (denoted as HPG, 6% HPG, approximately 402 mOsmol/kg, pH 7.4) and electrolyte control (denoted as Control, 251 mOsmol/kg, pH 7.4) solutions were prepared as reported previously .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PYS (Physioneal™ 40 solution, 2.27% glucose w/v) and ICO (Extraneal™, 7.5% icodextrin w/v) were purchased from Baxter Healthcare Co. (Deerfield, IL, USA). HPG (1 kDa) was synthesized by an anionic ring opening multibranching polymerization and characterized following our previous reports . A HPG PD solution (denoted as HPG, 6% HPG, approximately 402 mOsmol/kg, pH 7.4) and electrolyte control (denoted as Control, 251 mOsmol/kg, pH 7.4) solutions were prepared as reported previously .…”
Section: Methodsmentioning
confidence: 99%
“…Obese diabetic rats received a once‐daily IP injection of 10 mL of the PD solution or Control as previously established in our laboratory . In brief, after anaesthesia with isoflurane, 10 mL of a pre‐warmed PD solution (Control, PYS, ICO or HPG) was slowly injected into the peritoneal cavity at the abdominal midline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the molecular properties of HPG make it more efficient than glucose in producing ultrafiltration. Promising studies [15, 16] in rodents showed better preservation of UF and fewer toxic effects on the peritoneal membrane. However, studies in humans have not yet been conducted, and there are several questions remaining such as the ramifications of accumulation of HPG over time, or whether HPG molecules are metabolized in plasma and in the peritoneal cavity.…”
Section: Hyperbranched Polyglycerolmentioning
confidence: 99%
“…However, studies in humans have not yet been conducted, and there are several questions remaining such as the ramifications of accumulation of HPG over time, or whether HPG molecules are metabolized in plasma and in the peritoneal cavity. Also, the long-term biocompatibility over years remains unclear, with the longest animal experiment using the solution for 3 months [15]. …”
Section: Hyperbranched Polyglycerolmentioning
confidence: 99%